C.H.D. Clarke (1909-1981) - Norment, Christopher (ARCTIC, 1988)
Clarke was born on 14 June 1909 in Kerwood, Ontario, the son of a Methodist minister. As he described it, an early interest in natural history led him to become "a bird watcher, and in time a hunter, and then also a collector, and the lines of least resistance made me a wildlife biologist." [Clarke is best known for his work on the Thelon Game Sanctuary] . presented in A Biological Investigation of the Thelon Game Sanctuary. Although the report had value as the first systematic and complete list of barren-ground vertebrates, it also provided important information on wildlife use by Inuit and northern Indians, the population cycles of fur-bearing mammals, and caribou and muskoxen. In the section on caribou, Clarke examined the contemporary lack of scientific knowledge about northern wildlife. . In many ways, Clarke's ideas were ahead of his time. He argued for increased study and protection of caribou, abandoning preconceived ideas about predators, favoring native interests over those of whites in decisions regarding wildlife and discarding ineffectual and misguided wolf control programs. . In the conclusion he wrote, "We should always be careful that in our search for new resources we do not destroy what we already have. If we can keep it [the North] a true wilderness, its spiritual value will remain, but if the wild herds are lost it will not be a wilderness, but a desert." . A pioneer in biological research in the North, C.H.D. Clarke lived to see the region transformed by social, political, economic and technological forces. He recognized his good fortune at having been active "When things were still fresh" and was reluctant to return to places he once knew, for fear that they would have been destroyed. Near the end of his life he wrote, "To me the Sanctuary will always be what it was in my time." .